THE CORRELATION BETWEEN CHATTING ONLINE AND STUDENTS’ SPEAKING ACHIEVEMENT - Essa Widya Pangestika; Sri Nariah (PROJECT (Professional Journal of English Education), 2018)
The aim of this research is to figure out the correlation between chatting online and students’ speaking achievement. The method of this research was correlation method. The researchers used this research because they wanted to find out the degree of relationship students chatting online and their speaking skill achievement in English Education Department of IKIP Siliwangi in the academic year 2015. The data were gathered from the questionnaires and speaking tests, then were analyzed by Spearman Rank in SPSS V.23. The result showed that the score of Spearman Rank test is 0.299. It was defined that there is low correlation between two variables. In other words, there was no significance correlation between students chatting online and their speaking achievement.